HUBUNGAN PENGETAHUAN IBU (AKSEPTOR) DENGAN KEPATUHAN DALAM MELAKUKAN PENYUNTIKAN ULANG DI PUSKESMAS SIKUMANA KOTA KUPANG - Mita Paulus (STIKes CHMK, 2018)
ABSTRACT The using of contraception injected device is very interested by the women’s in the world and national, The use of contraception injection is popular among acceptor both in national setting or even in the world. contraception usage is higher than the usage of the froms of contraception. the purpose of this study was to know the correlation between woman’s knowledge (acceptplianor) with comce to re-injecting in Sikumana Health Service Center, Kupang City. This research is quantitative with cross sectional design. The sampling technique used was purposive sampling. The respondents in this study were all woman (acceptor) who did re-injection at Sikumana Health Service Center, Kupang City in total 82 people. Statistic test used was chi-square test with significance level α = 0.05. Statistical analysis shows that p value for compliance knowledge is 0,586 (p value <α) while for the conclusion of this research, knowledge has nothing to do with compliance for re-injection at Sikumana Health Service Center, Kupang City. Based on this research, information about contraception injection is very useful for acceptors as it can encourage them to be more compliant for reinjection Keywords: Knowledge, Compliance, Contraception Injected Device